Clifford goes to Kindergarten - Bridwell; Norman (New York Scholastic Inc, 2020)
"Clifford joins Emily Elizabeth for her first day of kindergarten. Emily Elizabeth is nervous about making new friends and missing home. But with Clifford by her side in class to sing songs and play games, Emily Elizabeth learns how much fun kindergarten can be!"